PEMANFAATAN MEDIA PEMBELAJARAN WORDWALL SEBAGAI EVALUASI PEMBELAJARAN PADA MAHASISWA PENDIDIKAN AGAMA ISLAM - Mardhiyah, Ainatul (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
In the digital era, learning activities must be able to adapt to technological and information developments. Educators must be able to develop learning media in creative and innovative ways, including in providing evaluations of the material that has been taught. Educational statistics as a compulsory subject for students of Islamic religious education, most of whom have social backgrounds, must be able to create an interesting and enjoyable atmosphere for students. This research method is descriptive qualitative, where the data source was obtained from students of the Islamic Religious Education study program who were taking an Educational Statistics course. The results of this study indicate that 94.6% of students' understanding by using WordWall said that WordWall was able to help remember learning material and 97.4% said that the educational game Wordwall was able to give a pleasant impression when working on quizzes or practice questions. Through the use of Wordwall , student interest in studying educational statistics courses has been shown to increase and suppress student saturation in learning the material being taughtAbstrakPada era digital, kegiatan pembelajaran harus mampu beradaptasi dengan perkembangan teknologi dan informasi. Pendidik harus mampu mengembangkan media pembelajaran dengan cara kreatif dan inovatif, termasuk dalam memberikan evaluasi dari materi yang telah diajarkan. Stasitika pendidikan sebagai mata kuliah wajib bagi mahasiswa pendidikan agama islam yang kebanyakan berlatar belakang dari jurusan social, harus mampu menciptakan suasana yang menarik dan menyenangkan bagi mahasiswa. Metode penelititan ini adalah kualitatif deskriptif, dimana sumber data diperoleh dari mahasiswa program studi Pendidikan Agama Islam yang sedang menempuh mata kuliah statistika Pendidikan. Hasil penelitian ini menunjukkan bahwa pemahaman mahasiswa dengan menggunakan WordWall sebesar 94,6 % mahasiswa mengatakan bahwa WordWall mampu membantu mengingat materi pembelajaran dan 97,4% mengatakan bahwa game edukasi Word wall mampu memberikan kesan menyenangkan ketika mengerjakan quiz ataupun latihan soal. Melalui pemanfaatan Wordwall, minat mahasiswa dalam mempelari matakuliah statistika pendidikan terbukti meningkat dan menekan kejenuhan mahasiswa dalam mempelajarai materi yang diajarkan.